Peran BAPEPAM dan Lembaga Profesi Penunjang Dalam Pengendalian Pasar Modal - Suryadi Suryadi (Jurnal Selat, 2015)
Lattely, the businessmen’s society had realized more about the function of capital market for their bussinesses development, that’s right, the investors require information about the situation of company as the basic consideration in commiting decision to invest. The information which is served in prospect that is published when the company commited public negotiation for capital market instrument to the society, basically contains description about the situation of company, which is observed from several aspects of law, finance, production industry, and marketing. however, another think that is also need to be attention in the capital market’s activity is how important the law inforcement’s improvement is for the violations they did. This is the taste of BAPEPAM and supportime profession institution to anticipate or to organize an inspection to every suspect for commiting or contributed in the violation. in this examination, the writer discusses about the rule of BAPEPAM and supportive profession institution of BAPEPAM in capital market’s activity. The used examination method is normative juridic method, an examination which oppresses in secondary data by examining and studying the foundations of law, especially the rules of positive law from literature materials in the rule of legislation and the valid term, especially that is related to the capital market, based on the analysis result and discussion, it is concluded that in the capital market’s activity, BAPEPAM acts as the organizing institution or as a faster-father of capital market’s actors by giving reaction if the exchange activity is weak, straightening if the capital market’s actors have deviated from the served lines, and executing law sanction if they violate the terms. And also need to be paid with attention to create a better quality of capital market, then the capital market’s activity demands participation from supportive profession institutions, especially in ‘’go public’’ process, because all activities which is related to capital market’s activity. The suportive professiob institutions are public accountant, notary, law consultant, appraiser, investment advisor. Key words : Capital Market, BAPEPAM, Supportive Profession Institutions